Mannitol-Coated Hydroxypropyl Methylcellulose as a Directly Compressible Controlled Release Excipient for Moisture-Sensitive Drugs: A Stability Perspective - Kang, Christina Yong Xin; Chow, Keat Theng; Lui, Yuan Siang; Salome, Antoine; Boit, Baptiste; Lefevre, Philippe; Hiew, Tze Ning; Gokhale, Rajeev; Heng, Paul Wan Sia (Pharmaceuticals (Basel, Switzerland), 2024)
Background/Objectives: Hydroxypropyl methylcellulose (HPMC) is one of the most commonly used hydrophilic polymers in formulations of matrix tablets for controlled release applications. However, HPMC attracts moisture and poses issues with drug stability in formulations containing moisture-sensitive drugs. Methods: Herein, the moisture sorption behavior of excipients and drug stability using aspirin as the model drug in matrix tablets were evaluated, using HPMC and the newly developed mannitol-coated HPMC, under accelerated stability conditions (40 °C, 75% relative humidity) with open and closed dishes. Results: Tablets prepared with mannitol-coated HPMC showed a slower drug degradation rate compared to tablets prepared with directly compressible HPMC. Initial moisture content and hygroscopicity were stronger predictors of drug stability compared to water activity when comparing samples without similar moisture content. In the early stage (day 0 to 30), the aspirin degradation rate was similar in both open and closed conditions, as moisture content is the main degradation contributor. In the later stage (day 30 to 90), aspirin degradation was faster under closed conditions than under open conditions, likely due to autocatalytic effects caused by the volatile acidic by-product entrapped in the closed environment. Conclusions: The findings from this study reinforced the importance of judicious excipient selection based on the understanding of excipient–moisture interactions to maximize the chemical stability of moisture-sensitive drugs. Mannitol-coated HPMC is a promising addition to the formulator’s toolbox for the formulation of controlled release dosage forms by direct compression.